Diphtong Monophtongization in Japanese Loanwoards: An Acoustic and Sociolinguistic Analysis of Language Contact Effects - Nursyifa Azzahro; Naelul Rohmah; Mauldina Permata Dewi; Alvyna Febrianti (Universitas Pendidikan Mandalika, 2026)
This study explores the monophthongization of diphthongs in Japanese loanwords, with a particular focus on the role of foreign language contact. Previous studies have failed to integrate acoustic evidence with sociolinguistic perception in explaining phonological adaptation in Japanese loanwards. This study fills this gap by integrating acoustic phonetic analysis and sociolinguistic perspectives. The dataset consists of 50 Japanese loanwords containing diphthongs (/ai/, /ei/, /oi/, /au/, /ou/), produced by 50 native speakers from two age groups (18–35 and 36–70). A total of 2,500 audio tokens were collected and analyzed using Praat to observe vowel duration and formant transitions. In addition, a perception survey was conducted to assess speakers' attitudes toward monophthongization. The findings indicate a systematic shift from dynamic vowel sequences toward stable long vowel nuclei, suggesting that Japanese speakers are not merely simplifying articulation but restructuring diphthongal sequences into phonologically unified segments. These findings challenge the traditional assumption that Japanese preserves vowel sequences without significant restructuring, suggesting instead that loanward phonology actively reshapes vowel organization under contact pressure. Sociolinguistic results show diverse perceptions: some consider this process natural, while others see it as an impact of media and globalization. The generational differences observed in this stud suggest that monophthongization is not a completed change but a stratified variation, where competing phonetic norms coexist across age groups. This study contributes to the understanding of sound changes in Japanese, supports language education, and provides a curated phonetic dataset for future linguistic and speech technology research.